Clinician‐Patient Small Talk: Comparing Fourth‐Year Dental Students and Practicing Dentists in a Standardized Patient Encounter. Issue 11 (1st November 2016) - Maupome, Gerardo; Holcomb, Christopher; Schrader, Stuart
Abstract : The aim of this study was to establish whether frequency of non‐diagnostic, non‐management exchanges between clinicians and patient (called "socioemotional communication, " SC) during a consultation differed between fourth‐year dental students and dentists, controlling for clinically driven exchanges of information. Fifteen dentists and 17 fourth‐year dental students were recorded in 2006 while undergoing a consultation with a live standardized patient and were subsequently interviewed by investigators in a separate room with the recording present for analysis. Their shared interpretations of cognitive strategies were recorded and compared for differences in the presence of SC. The results showed that most of the students and dentists engaged in SC throughout the consultation with a few exceptions. There were no significant differences between student and dentist cohorts for overall SC presence (p=0.62), time to first instance of SC from overall start of the consultation (p=0.73), and time to first instance of SC after first intraoral examination had taken place (p=0.76). Nonsignificant differences were also recorded for overall frequency at which SC occurred from overall start of the consultation (p=0.89) and after the first intraoral examination had taken place (p=0.12). The patterns showed SC interaction occurring throughout the consultation, not concentrated at the beginning or end. SC did not appear to differ between practitioners and students in terms of prevalence, frequency, or timing. Future research should examine the detailed association between SC and diagnostic thinking processes to further delineate the relationship and characterize possible pedagogical applications.